Numerical Modelling Of Synthetic-Jet-Assisted Mixing - Cheng, See Yuan; Hong, Mun Hoh; Lim, Kim Chuan (Penerbit Akademia Baru, 2019)
The aim of the present study is to develop a Computational Fluid Dynamics (CFD) model of synthetic-jet-assisted fluid mixer. A geometric model which consists of a mixing channel with a pair of synthetic jet actuators was created. The diaphragm motion of the synthetic jet actuators was realized by a moving mesh method. Dye solution and water were introduced into the fluid mixer from two different inlets. Mixing degree was numerically predicted as the result of the CFD model. Verifications were performed to examine the sensitivity of the model to temporal and spatial resolutions. The results were validated against experimental data and a good agreement was achieved. The overall results indicated that the time-step size affected the mixing degree significantly. The mesh resolution only has slight influence on the mixing degree.